Empowering the Marginalized through the Halal Industry in Indonesia: A Systematic Literature Review - Nuryanto, Uli Wildan; Basrowi, Basrowi; Quraysin, Icin; Pratiwi, Ika; Utami, Pertiwi (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to conduct a systematic literature review on the themes of equality and social justice for people with disabilities in Indonesia, with a specific focus on their intersection with community empowerment within the halal industry. Using empirical evidence and bibliometric analysis, the review applies the keywords "equality and social justice," "people with disabilities," and "sharia economic empowerment" to explore relevant literature. Data were collected through the Publish or Perish tool, identifying over 1,000 academic publications from 2014 to 2024, and visualized using VOSviewer. The findings highlight two key points: first, while various regulations, policies, and flagship programs have sought to promote equality and social justice for people with disabilities, their implementation remains suboptimal in ensuring the full realization of rights. Second, empowerment strategies rooted in sharia economic models emphasize the transformation of negative mindsets and the adoption of Islamic entrepreneurial approaches. Notably, there was a significant decline in research interest from 2014 to 2021, followed by a resurgence through 2023. These insights offer a valuable reference for policymakers and stakeholders to design more effective initiatives aimed at enhancing the quality of life for people with disabilities through inclusive economic empowerment.======================================================================================================== ABSTRAK - Pemberdayaan Kelompok Marjinal melalui Industri Halal di Indonesia: Sebuah Tinjauan Literatur Sistematis. Penelitian ini bertujuan untuk melakukan tinjauan literatur sistematis mengenai tema kesetaraan dan keadilan sosial bagi penyandang disabilitas di Indonesia, dengan fokus yang spesifik pada interaksinya dengan pemberdayaan masyarakat dalam konteks industri halal. Dengan menggunakan bukti empiris dan analisis bibliometrik, kajian ini menggunakan kata kunci "kesetaraan dan keadilan sosial," "penyandang disabilitas," dan "pemberdayaan ekonomi syariah" untuk menelusuri literatur yang relevan. Data dikumpulkan melalui perangkat “Publish or Perish”, yang mengidentifikasi lebih dari 1.000 publikasi ilmiah selama periode 2014 sampai 2024, dan divisualisasikan dengan aplikasi VOSviewer. Hasil analisis menunjukkan dua poin utama: pertama, meskipun telah ada berbagai regulasi, kebijakan, dan program unggulan untuk mendorong kesetaraan dan keadilan sosial bagi penyandang disabilitas, pelaksanaannya belum sepenuhnya mampu memenuhi hak-hak mereka secara optimal. Kedua, strategi pemberdayaan yang berbasis pada model ekonomi syariah menekankan pada transformasi pola pikir negatif dan pendekatan kewirausahaan Islami. Secara signifikan, terdapat penurunan minat penelitian dalam topik ini selama 2014–2021, namun kembali meningkat hingga tahun 2023. Temuan ini memberikan referensi penting bagi para pembuat kebijakan dan pemangku kepentingan dalam merancang inisiatif yang lebih inklusif untuk meningkatkan kualitas hidup penyandang disabilitas melalui pemberdayaan ekonomi yang berkeadilan.